2006
DOI: 10.1111/j.1745-7254.2006.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of DRD2 polymorphisms and chlorpromazine-induced extrapyramidal syndrome in Chinese schizophrenic patients1

Abstract: Aim: Extrapyramidal syndrome (EPS) is most commonly affected by typical antipsychotic drugs that have a high affinity with the D2 receptor. Recently, many research groups have reported on the positive relationship between the genetic variations in the DRD2 gene and the therapeutic response in schizophrenia patients as a result of the role of variations in the receptor in modulating receptor expression. In this study, we evaluate the role DRD2 plays in chlorpromazineinduced EPS in schizophrenic patients. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
2
10
2
Order By: Relevance
“…Notably, our data do not support the view that genetic variations of the DRD2 gene significantly predispose to AIPwhen measured as a total syndrome-and hence do replicate findings of three other studies in German [Kaiser et al, 2002] and Asian [Chong et al, 2003;Wu et al, 2006] patients, respectively. However, we do find a significant association between rigidity and the DRD2 promoter variant -141CIns/ Del, which-although debated [Pohjalainen et al, 1999;Ritchie and Noble, 2003]-has been suggested to be functional [Arinami et al, 1997;Jonsson et al, 1999] or in linkage disequilibrium with another functional polymorphism [Duan et al, 2003].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Notably, our data do not support the view that genetic variations of the DRD2 gene significantly predispose to AIPwhen measured as a total syndrome-and hence do replicate findings of three other studies in German [Kaiser et al, 2002] and Asian [Chong et al, 2003;Wu et al, 2006] patients, respectively. However, we do find a significant association between rigidity and the DRD2 promoter variant -141CIns/ Del, which-although debated [Pohjalainen et al, 1999;Ritchie and Noble, 2003]-has been suggested to be functional [Arinami et al, 1997;Jonsson et al, 1999] or in linkage disequilibrium with another functional polymorphism [Duan et al, 2003].…”
Section: Discussioncontrasting
confidence: 70%
“…Studies focusing on HTR2A and HTR2C pharmacogenetics and AIP are currently scarce [Hamdani et al, 2005;Gunes et al, 2007]. Furthermore, there are currently only a few studies evaluating extensive sets of DRD2-polymorphisms in connection with AIP [Kaiser et al, 2002;Nakazono et al, 2005;Wu et al, 2006] and none were conducted in Negroid patients.…”
Section: Introductionmentioning
confidence: 97%
“…This study also reports an association between TaqI_D and akathisia. This intronic SNP has previously only been investigated for tardive dyskinesia (Kaiser et al 2002;Wu et al 2006;Zai et al 2007) and was significantly associated in a two-marker haplotype with C939T (Zai et al 2007). Although the pathophysiology of akathisia is still largely unknown, there is clinical evidence that medication interfering with the dopamine system and leading to a low dopaminergic tone is associated with the insistent feeling of restlessness and the urge to move Marsden and Jenner 1980).…”
Section: Discussionmentioning
confidence: 96%
“…This polymorphism may alter substrate-binding specificity (Neville, 2004). Most studies that have investigated genetic variants of the DRD2/ANKK 1 Taq1A polymorphism find that there is no association with EPS, in patients who were treated with first generation antipsychotics (FGAs) (Kaiser et al, 2002;Wu et al, 2006). Only one single study reports a positive association (Güzey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%